Invoking students thinking in engineering mathematics through informal cooperative learning - Abdul Rahman, Roselainy (2015)
Most engineers recognize the powers of mathematical thinking that gives them a means of formulating, analyzing and solving a wide range of practical problems. We have been working to support and enhance students’ mathematical thinking powers in mathematics learning. A framework was developed based on the work of Mason et al (1982, 2010), Watson & Mason (1998), and Tall (1993, 1995) to make the thinking processes and the structures of mathematics explicit as well as increasing students’ awareness on the use of their thinking powers. See Roselainy et al. (2007), Baharun et al. (2008), Roselainy (2009) and Roselainy et. al. (2012) for details. The framework was further extended to include students’ Self-Regulated Learning (SRL). The Teaching and Learning Model (see Figure 1) categorizes the learning situation into three components, (1) the course learning outcomes, (2) the teaching and learning and assessment (TLA) activities and tasks and (3) the environment supporting the SRL processes (Roselainy et al., 2014).